Faktor Yang Mempengaruhi Atribusi Laba Dan Ekuitas Perusahaan Food And Beverage Di Indonesia - Purwanti, Asih Tugi; Kusuma, Marhaendra; Selviasari, Rike (JCA (Jurnal Cendekia Akuntansi), 2023)
Since PSAK has converged with IFRS, the contents of the income statement format are not only net income, but also other comprehensive income and attribution of profit. The latest statement of financial position contains additional information, namely equity attributable to owners of the parent entity and non-controlling interests. The aim of this research is to provide evidence from observations and discovery of the factors behind the profit and equity values attributed to owners. The population is 27 companies in the food & beverage sub-sector. A sample of 16 companies, with 48 observational data. The findings of the investigation prove that profitability has a positive effect on profits attributable to owners of the parent entity, while the percentage of controlling share ownership and the percentage of non-controlling share ownership has a negative effect on profits attributed to owners of the parent entity. The number of subsidiaries has a positive effect on profits attributable to non-controlling interests, while the percentage of controlling share ownership as well as the percentage of non-controlling share ownership has a negative effect on profits and equity attributable to non-controlling interests. Net sales have a positive effect on equity attributable to the parent entity, while profitability, operating cash flow, percentage of controlling share ownership, percentage of non-controlling share ownership, company size, and number of subsidiaries have no effect on equity attributable to owners of the parent entity. The number of subsidiaries has a positive effect on equity attributable to non-controlling interests, while net sales, operating cash flow, and company size have a negative effect on equity attributable to non-controlling interests